2006
DOI: 10.1074/jbc.m508649200
|View full text |Cite
|
Sign up to set email alerts
|

The 2′,5′-Oligoadenylate Synthetase 1b Is a Potent Inhibitor of West Nile Virus Replication Inside Infected Cells

Abstract: The 2,5-oligoadenylate synthetase (OAS) proteins associated with endoribonuclease RNase L are components of the interferonregulated OAS/RNase L system, which is an RNA decay pathway known to play an important role in the innate antiviral immunity. A large body of evidence suggests a critical role for the 1b isoform of the mouse Oas gene (Oas1b) in resistance to West Nile virus (WNV) infection in vivo. WNV is a positive, single-stranded RNA virus responsible for severe encephalitis in a large range of animal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 32 publications
3
78
0
Order By: Relevance
“…Furthermore, genetic knock-in of the Oas1b resistance allele into a susceptible mouse strain confers resistance to the yellow fever virus (8). In vitro data also show that cells expressing wild-type OAS1b but not C-terminally truncated OAS1b efficiently block WNV replication (9,10). Thus, in vivo and in vitro experiments indicate that mouse Oas1b is an important genetic factor in flavivirus resistance.…”
Section: Engue Virus (Den)mentioning
confidence: 63%
“…Furthermore, genetic knock-in of the Oas1b resistance allele into a susceptible mouse strain confers resistance to the yellow fever virus (8). In vitro data also show that cells expressing wild-type OAS1b but not C-terminally truncated OAS1b efficiently block WNV replication (9,10). Thus, in vivo and in vitro experiments indicate that mouse Oas1b is an important genetic factor in flavivirus resistance.…”
Section: Engue Virus (Den)mentioning
confidence: 63%
“…The NS3/4A protein complex of hepatitis C virus also blocks phosphorylation of IRF3 (34). Among the ISG, the antiviral activity of 2Ј5ЈOAS has been wellcharacterized (35,36), however, the complete spectrum of ISG with potential antiviral activity remains to be defined. In this context, it is of interest to note that the microarray analysis of our pIC-activated astrocytes identified viperin/cig5 as one of the most highly expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…2 -5 -Oas1b is also a potent inhibitor of WNV replication in infected cells. 39 The role of the Oas system in human susceptibility to WNV infection is unknown. In one recent study, however, differences were observed in the frequency distribution of at least one polymorphism in OAS genes in hospital ized patients with WNV infection compared with controls, raising the possibility that the Oas system also has a role in human susceptibility to WNV infection.…”
Section: Risk Factorsmentioning
confidence: 99%